HYBRIDIZATION, NATURAL SELECTION, AND EVOLUTION OF REPRODUCTIVE ISOLATION: A 25‐YEARS SURVEY OF AN ARTIFICIAL SYMPATRIC AREA BETWEEN TWO MOSQUITO SIBLING SPECIES OF THE Aedes mariae COMPLEX. (1st October 2014) - Urbanelli, Sandra; Porretta, Daniele; Mastrantonio, Valentina; Bellini, Romeo; Pieraccini, Giuseppe; Romoli, Riccardo; Crasta, Graziano; Nascetti, Giuseppe
Abstract: Natural selection can act against maladaptive hybridization between co‐occurring divergent populations leading to evolution of reproductive isolation among them. A critical unanswered question about this process that provides a basis for the theory of speciation by reinforcement, is whether natural selection can cause hybridization rates to evolve to zero. Here, we investigated this issue in two sibling mosquitoes species, Aedes mariae and Aedes zammitii, that show postmating reproductive isolation (F1 males sterile) and partial premating isolation (different height of mating swarms) that could be reinforced by natural selection against hybridization. In 1986, we created an artificial sympatric area between the two species and sampled about 20, 000 individuals over the following 25 years. Between 1986 and 2011, the composition of mating swarms and the hybridization rate between the two species were investigated across time in the sympatric area. Our results showed that A. mariae and A. zammitii have not completed reproductive isolation since their first contact in the artificial sympatric area. We have discussed the relative role of factors such as time of contact, gene flow, strength of natural selection, and biological mechanisms causing prezygotic isolation to explain the observed results.